Hereditary hemorrhagic telangiectasia: An overview of diagnosis and management in the molecular era for clinicians - Pinar Bayrak‐Toydemir; Rong Mao; Susan O. Lewin; Jamie McDonald (2004)
Hereditary hemorrhagic telangiectasia (Osler-Weber-Rendu syndrome) is a relatively common, underdiagnosed autosomal-dominant disorder of arteriovenous malformations and telangiectases. DNA testing for hereditary hemorrhagic telangiectasia has recently become available in North America, making presymptomatic screening available to relatives with a positive molecular diagnosis. This now enables practitioners to prevent catastrophic complications of undiagnosed pulmonary and CNS arteriovenous malformations and eliminates the need to radiographically screen all at-risk relatives shown to be unaffected by molecular testing. We review the clinical aspects of hereditary hemorrhagic telangiectasia, describe the indications, benefits, and limitations of molecular diagnostic testing for hereditary hemorrhagic telangiectasia, and provide a molecular genetics summary to facilitate genetic counseling before and after DNA testing for this complex disorder.